Analisis Wacana Kritis Berbasis Teknologi Informasi dan Komunikasi di Komunitas Sekolah untuk Menangkal Berita Hoaks - Herli Salim; Widjojoko Widjojoko; Muhammad Hanif (Jurnal Pengabdian Masyarakat PGSD, 2021)
Preventing community from hoaxes is essential in the information disruptive era. During the social distancing policy due to COVID-19 outbreaks, the hoaxes deployment was raised in line with the high social media utilization.  School community is one of the susceptible societies on hoaxes deployment. This community service program aimed to train the school community a skill to identify and report hoax information using critical discourse analysis assisted by ICT tools. The program was conducted in Pilot Laboratory Elementary School of Universitas Pendidikan Indonesia at Serang Campus. The location was selected based on the preliminary assessment on the high risk of hoaxes deployment among the teacher and students’ parents during the learning from home activity. The program was executed in a seminar and workshop of optimizing critical discourse analysis using ICT. The program was developed by ASSURE model adapted in Pre-Program, In-Program, and Post-Program activities. The result of this empowerment was the instillment of identifying and reporting the hoaxes information. After the program, the participations were able to analyze the hoxes information characteristics and utilize android-based software to report it to the authorized party. The follow up program was invited the community to be a part of anti-hoax citizen community